The role of gut microbiome in colorectal cancer development: a comprehensive analysis based on metabolomics and immunomodulatory mechanisms - Xu, Yichi; Wen, Bo; Liu, Shu (Frontiers in Oncology, 2025)
With shifts in lifestyle and dietary habits, the incidence of colorectal cancer has been rising annually, with an increasing prevalence among younger populations, thereby imposing a significant burden on global health. Although the rate of early diagnosis for colorectal cancer has improved due to the widespread use of gastrointestinal endoscopy, many patients still do not experience substantial improvements in survival rates or quality of life. Consequently, there is a pressing need for further in-depth research into the pathogenesis of colorectal cancer, as well as the exploration of potential methods for early diagnosis and precise treatment. As research into the gut microbiome system advances, its remarkable efficacy in the early diagnosis, treatment, and prognosis assessment of various diseases has garnered considerable attention. Variations in the gut microbiome among individuals may result in differential immune responses to specific pathogens or treatment modalities. This article reviews the interaction mechanisms between gut microbiota and immune cells in colorectal cancer, integrating the latest research findings in the field, with the aim of providing potential directions and theoretical foundations for the development of personalized immunotherapy.